Revisión de las provisiones existentes para diafragmas en construcción prefabricada a partir del reglamento NSR-10 (2016)
The main objective of the research was to determine whether the behavior of mezzanines in precast structure due to a system of rigid diaphragm, semi-rigid or flexible, in the same way we studied whether the accelerations estimated to expressions of regulations NSR-10, they may be applicable to this type of construction, for which it was necessary to find indicators of analysis and design for diaphragms prefabricated panels constructed using reinforced concrete solid plate and united in place by reinforcing soldier. From conducting laboratory tests with loads applied normal to the plane and the plane of specimens to scale a plate portion afferent containing a typical connection, through modeling in software specialized in finite element, theories contact and the analysis and design of buildings, research obtained as a result acceptable performance of the connection and a rigid diaphragm behavior in a typical structure of 5 floors subjected to a chronological dynamic analysis with five different accelerograms representative of the threat of Bogota.